La scène économique et financière nord-américaine en 1987 - Fortin, Franceline (Assurances, 1988)
The year 1987 has not only been one of major economic and financial activity, but also the year of the stock market crash which deeply affected all of us. Though some indices remain favourable, the optimism which prevailed prior to the crash has given way to uncertainty and hesitation. If the situation on the international scene is not worrisome, it is, however, quite disturbing. There is a pressing need for leading industrialized nations to coordinate their economic policies. The circumstances which precipitated the market into turmoil are clear: the United States are living beyond their means. Moreover, are they not the world's bankers? Will they ever be again? Who knows?